How aminoacyl-tRNA synthetases translate the genetic code - Cusack, Stephen (Henry Stewart Talks, 2008)
Fidelity of protein synthesis, Architecture of aminoacyl-tRNA synthetase, ATP and amino acid recognition by the two classes of synthetases, The activation reaction, Cognate tRNA recognition by synthetases, The aminoacylation reaction, Direct and indirect routes to aminoacylation, Error correction (editing) by aminoacyl-tRNA synthetases, Aminoacyl-tRNA synthetases as antibiotic targets
Reviewed at 2020/08/12